2019
DOI: 10.1021/acs.accounts.9b00234
|View full text |Cite
|
Sign up to set email alerts
|

From Optical to Chemical Hot Spots in Plasmonics

Abstract: In recent years, the possibility to induce chemical transformations by using tunable plasmonic modes has opened the question of whether we can control or create chemical hot spots in these systems. This can be rationalized as the reactive analogue of the well-established concept of optical hot spots, which have drawn a great deal of attention to plasmonic nanostructures for their ability to circumvent the far-field diffraction limit of conventional optical elements. The parameters that determine the reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
171
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(179 citation statements)
references
References 78 publications
3
171
0
5
Order By: Relevance
“…[146] In order to achieve an absorption dominated by Landau damping, it is also recommended to use nanostructures with dimensions below the electrons mean free path length. [146,151] For gold and silver, this criterion applies to particles with a diameter smaller than 30 nm. In this size range little scattering is to be expected and interactions are preferentially located at the surface.…”
Section: Hot Charge Carrier Generation and Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…[146] In order to achieve an absorption dominated by Landau damping, it is also recommended to use nanostructures with dimensions below the electrons mean free path length. [146,151] For gold and silver, this criterion applies to particles with a diameter smaller than 30 nm. In this size range little scattering is to be expected and interactions are preferentially located at the surface.…”
Section: Hot Charge Carrier Generation and Transfermentioning
confidence: 99%
“…In the classical indirect transfer mechanism, hot electrons are first generated in the metal and then transferred to the LUMO of the adsorbed molecule. [151] Although this process is generally regarded as the dominant mechanism, recent studies suggest a second mechanism via a direct electron transfer pathway resulting from chemical interfacial damping (CID). [163] Experimental observations have shown that a material that is chemically bound to a plasmonic nanoparticle can lead to the acceleration of the plasmon dephasing and thus CID.…”
Section: Hot Charge Carrier Generation and Transfermentioning
confidence: 99%
“…Likewise, these metallic nanostructures can greatly enhance the photocatalytic activity of regular semiconductors given their plasmonic properties that facilitate the effective transport of hot carriers (i.e. hot electrons or hot holes) [26][27][28][29][39][40][41][42][43][44][45][46][47][48][49]. Another important topic of interest is currently devoted to the search for valid alternatives to TiO2 as semiconductor photocatalytic supports.…”
Section: Introductionmentioning
confidence: 99%
“…These volumes are usually referred to as optical hot-spots, as the electromagnetic eld can reach values magnitudes higher than the incoming light. [1][2][3][4] Such hotspots can be useful to enhance properties arising from the interaction of radiation with the nanostructure and the surrounding environment and are therefore applied, for example, to increase the local temperature, 5 catalyze chemical reactions, 4,[6][7][8] increase photovoltaic efficiency, 9 or increase spectroscopic signals. 10,11 The latter has been particularly useful in surface-enhanced Raman spectroscopy (SERS), 4 where optimized design of such hotspots has shown to be capable of the detection on the single-molecule level.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Two very recent reviews highlighted the use of plasmonic hot spots in chemical transformations and SERS, while underlining the demand for reliable methods for substrate fabrication. 4,8 An ideal nanostructure to take advantage of signal, energetic, or chemical enhancement should have the following properties. First, its structure should provide a high near-eld enhancement.…”
Section: Introductionmentioning
confidence: 99%